The associations of physical activity with fracture risk—a 7-year prospective controlled intervention study in 3534 children. Issue 3 (March 2016) - Fritz, J.; Cöster, M.; Nilsson, J.-Å.; Rosengren, B.; Dencker, M.; Karlsson, M.
Abstract Summary This is the first study indicating an association between gradually diminished risk of fractures and years of increased physical activity. Our results could imply great benefits not only for the individual but also for the healthcare burden and cost of society. Introduction Physical activity (PA) in childhood is associated with high bone mass and beneficial neuromuscular function. We investigate if increased PA also is associated with fracture risk. Methods We registered fractures in 3534 children aged 6 to 8 years at study start for up to 7 years; 1339 with 40 min of moderate PA every school day (intervention) and 2195 with the Swedish standard curriculum of 60 min of PA per school week (controls). In a subsample of 264 children, we measured areal bone mineral density (aBMD; g/cm2 ) with dual-energy X-ray absorptiometry (femoral neck and total spine) and muscle strength (peak torque for knee extension and flexion; Nm) with computerized dynamometer at baseline and after 7 years. We estimated annual fracture incidence rate ratios (IRR) in the intervention group compared to the control group as well as changes in bone mass and muscle strength. Data is given as mean (95 % CI). Results The IRR of fractures decreased with each year of the PA intervention (r  = −0.79;p  = 0.04). During the seventh year, IRR was almost halved [IRR 0.52 (0.27, 1.01)]. The intervention group had a statistically significant greater gain in total spine aBMD with a mean group difference of 0.03 (0.00, 0.05) g/cm2 and peak flexion torque 180° with a mean group difference of 5.0 (1.5, 8.6) Nm. Conclusions Increased PA is associated with decreased fracture risk, probably in part due to beneficial gains in aBMD and muscle strength.